2x - 6y = 12
so we pick any number for x and then solve for y
lets say x = 0
2(0) - 6y = 12
-6y = 12
y = -12/6
y = -2....so when x = 0, y = -2....(0,-2) <== one point
lets say x = 1
2(1) - 6x = 12
2 - 6x = 12
-6x = 12 - 2
-6x = 10
x = -10/6
x = - 5/3...so when x = 1, y = -5/3....(1,-5/3) <== another point
Lets say x = 2
2(2) - 6y = 12
4 - 6y = 12
-6y = 12 - 4
-6y = 8
y = -8/6
y = - 4/3....so when x = 2, y = -4/3.....(2,-4/3) <== another point
lets say x = 3
2(3) - 6y = 12
6 - 6y = 12
-6y = 12 - 6
-6y = 6
y = -6/6
y = -1....so when x = 3, y = -1.....(3,-1) <== another point
now there is 4 points.
Answer:
the change is 8.4 degrees
Step-by-step explanation:
1.2x7=8.4
Answer:
x=−2
Step-by-step explanation:
Answer:
x = 16
m<Y = 34°
Step-by-step explanation:
∆XYZ is an isosceles ∆. An isosceles ∆ has two equal sides, as well as the bases of the isosceles triangle are congruent. In this case, therefore:
<X = <Z
(6x - 23)° = (4x + 9)
Solve for x
6x - 23 = 4x + 9
Collect like terms
6x - 4x = 23 + 9
2x = 32
Divide both sides by 2
x = 16
m<Y = 180° - (m<X + m<Z) (sum of ∆)
m<Y = 180 - ((6x - 23) + (4x + 9))
Plug in the value of x
m<Y = 180 - ((6(16) - 23) + (4(16) + 9))
m<Y = 180 - (73 + 73)
m<Y = 34°
The answer is 164. 5x4=20 and so on